Reliance of building energy in various climatic regions using multi criteria - Alwetaishi, M.; Gadi, Mohamed; Issa, U.H. (Elsevier, 2017)
Selecting a ventilation system for a certain building has always been considered as one of the critical problems for designers. Kingdom of Saudi Arabia (KSA) is characterized by a large area of significant climatic changes. In this research, five criteria are identified to compare and select one of the most popular ventilation systems, mechanical or natural. The identified criteria include Energy efficiency in buildings, Building function, Thermal comfort, the Maintenance cost of building, and Microclimatic conditions. The use of a mechanical system may be useful for achieving the building function and thermal comfort, while it seems to be more expensive. On the other hand, the natural ventilation system saves energy in the long run but it may not meet a comfort level for many users. Three regions which cover most of the climatic variations in the country are selected as a case study. A Ventilation Decision Making Model (VDMM), depends on the Analytic Hierarchy Process (AHP) as a multi-criteria analysis technique, is proposed and developed. For feeding data to the VDMM, field measures for indoor air temperature and relative humidity are conducted as well as applying an energy simulation model to predict indoor energy performance in the selected regions. Based on the results of VDMM application on the investigated case study, a decision to KSA construction market is introduced. The results absolutely support using the mechanical system in both Riyadh and Jeddah regions while utilizing the natural system in Abha region is more preferable. The VDMM is characterized by its flexibility, accepting more alternatives or criteria and its validity to be applied to other regions inside or outside KSA.